Value of Wisdom Local Tradition Gewe Traditional Ceremony in the Dayak Community Kanayan - Hemafitria, Hemafitria; Rohani, Rohani; Rani, Rani; Rizal, Yenni; Wahab, Wahab (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to describe the local wisdom values of the Dayak Kanayatn community in the Gawe Padi traditional ceremony tradition in Tiang Aji Hamlet, Lamoanak Village . Activities that are customary in tradition are the basis for seeing the implementation of values that can form local character or values. Qualitative is the approach in research, the method used is descriptive. Data collection through observation and interviews, and documentation studies. This data analysis technique consists of three activity flows, namely data reduction, data presentation, conclusions . Based on the findings of the local wisdom of the Dayak Kanayatn community in the gawe padi traditional ceremony tradition, it is a traditional ceremony tradition that has noble values and as an expression of gratitude to God (Jubata) for the rice harvest produced in the implementation of the preparation and implementation stages. The values of local wisdom in the implementation of the gawe padi custom are found to have values of togetherness, family values, brotherhood values, justice values, voluntary values, responsibility values, mutual cooperation values, brotherhood values and unity in the life and environment of the community.